Systemic Epstein–Barr Virus-Positive T/NK Lymphoproliferative Diseases With SH2D1A/XIAP Hypomorphic Gene Variants - Ishimura, Masataka; Eguchi, Katsuhide; Shiraishi, Akira; Sonoda, Motoshi; Azuma, Yoshihiro; Yamamoto, Hiroyuki; Imadome, Ken-ichi; Ohga, Shouichi (Frontiers in Pediatrics, 2019)
X-linked lymphoproliferative disease (XLP) is one of the X-linked primary immunodeficiency diseases (PIDs) with defective immune response to Epstein–Barr virus (EBV) infection. Chronic active EBV infection (CAEBV) and EBV-hemophagocytic lymphohistiocytosis (HLH) are recognized as systemic EBV-positive T-cell and natural killer (NK)-cell lymphoproliferative diseases (LPDs) arising from the clonal proliferations of EBV-infected T cells and NK cells. A high incidence of CAEBV in East Asia implies the unknown genetic predisposition. In patients with XLP, EBV-infected cells are generally B cells. No mutation of SH2D1A/XIAP genes has ever been identified in patients with systemic EBV-positive T-cell and NK-cell LPD. We report herewith a male case of NK-cell type CAEBV with SH2D1A hypomorphic mutation (c.7G > T, p.Ala3Ser), two male cases of CAEBV/EBV-HLH with XIAP hypomorphic variant (c.1045_1047delGAG, p.Glu349del), and another female case of CD4+CAEBV with the same XIAP variant. The female underwent bone marrow transplantation from an HLA-matched sister with the XIAP variant and obtained a complete donor chimerism and a cure of laryngeal LPD lesion, but then suffered from donor-derived CD4+ T cell EBV-LPD. These observations demonstrated that SH2D1A and XIAP genes are critical for the complete regulation of EBV-positive T/NK cell LPD. X-linked lymphoproliferative disease (XLP) is one of the X-linked primary immunodeficiency diseases (PIDs) reported to have a defective immune response to Epstein–Barr virus (EBV) infection. Mutations in SH2D1A and XIAP genes cause XLP. Systemic EBV-positive T-cell and natural killer (NK)-cell lymphoproliferative diseases (LPDs) consist of three major types: EBV-positive hemophagocytic lymphohistiocytosis (HLH), chronic active EBV infection (CAEBV), and EBV-positive T-cell/NK-cell lymphoma. CAEBV is recognized as a poor prognostic disease of EBV-associated T-cell and NK-cell LPD arising from the clonal proliferation of EBV-infected T cells (CD4+, CD8+, and TCRγδ+) and/or NK cells. The majority of cases with CAEBV were reported from East Asia and South America. In Caucasian patients with CAEBV disease, the target of infection is exclusively B cells. These imply a genetic predisposition to EBV-positive T/NK cell LPD according to ethnicity. In reported cases with XLP, EBV-infected cells are B cells. On the other hand, no mutation of SH2D1A/XIAP genes have been determined in patients with T/NK-cell-type (Asian type) CAEBV. We here describe, for the first time, four case series of CAEBV/EBV-HLH patients who carried the hypomorphic variants of XLP-related genes. These cases included a male patient with CAEBV carrying SH2D1A hypomorphic mutation (c.7G > T, p.Ala3Ser) and two male patients with CAEBV/EBV-HLH carrying the XIAP hypomorphic variant (c.1045_1047delGAG, p.Glu349del), along with another female patient with CAEBV carrying the same XIAP variant. The female case underwent bone marrow transplantation from a healthy HLA-matched sister having the same XIAP variant. Although a complete donor chimerism was achieved with the resolution of laryngeal LPD lesions, systemic donor-derived CD4+ T-cell EBV-LPD developed during the control phase of intractable graft- vs. -host-disease. These observations demonstrated that SH2D1A and XIAP genes are critical for the complete regulation of systemic EBV-positive T/NK-cell LPD.